The Trilogy of Dactylography, Cheiloscopy and BloodgroupsA Futuristic AID in Forensic Investigations - Jobby, Abraham; Naik, Lohit (Biology, Engineering, Medicine and Science Reports)
Personal Identification is of paramount importance not only in legal medicine but also in medico-legal investigation and genetic research. Identification means the determination of the individuality of a person. The use of prints as a mean of personal identification is one of the common methods in forensic anthropology and the most popular prints are fingerprints and lip prints, which are normal lines and fissures in the form of wrinkles and grooves present in the zone of transition of human lip. Theory of uniqueness and individualistic of the fingerprints and lip prints and co relationship with the blood group have been proven to be an imperative tool in identifying a person. Several studies have been carried out in these regard with most of the studies showing a significant co relationship between the fingerprints and the blood group with only handful of studies showing co relationship among fingerprints, lip prints and blood group. The pattern of fingerprints and lip prints were shown to be stable relative to surrounding anatomy and with passage of time and also in its easiest way of recording and documentation.